Altered NKp30, NKp46, NKG2D, and DNAM-1 Expression on Circulating NK Cells Is Associated with Tumor Progression in Human Gastric Cancer - Bin Han; Fang-yuan Mao; Yong-liang Zhao; Yi-pin Lv; Yong-sheng Teng; Mubing Duan; Weisan Chen; Ping Cheng; Ting-ting Wang; Zhong-yuan Liang; Jin-yu Zhang; Yu-gang Liu; et al. (Journal of Immunology Research)
Natural killer (NK) cell activity is influenced by a complex integration of signaling pathways activated downstream of both activating and inhibitory surface receptors. The tumor microenvironment can suppress NK cell activity, and there is a great clinical interest in understanding whether modulating tumor-mediated NK cell suppression and/or boosting preexisting NK cell numbers in cancer patients is therapeutically viable. To this light, we characterized the surface receptor phenotypes of peripheral blood NK cells and examined their clinical relevance to human gastric cancer (GC). We found that the proportion of peripheral blood NK cells which expressed the activating receptors NKp30, NKp46, NKG2D, and DNAM-1 was significantly decreased in GC patients compared to healthy donors, and that this decrease was positively associated with tumor progression. At the same time, plasma TGF-β1 concentrations were significantly increased in GC patients and negatively correlated with the proportion of NKp30, NKp46, NKG2D, and DNAM-1 expressing NK cells. Furthermore, TGF-β1 significantly downregulated the expression of NKp30, NKp46, NKG2D, and DNAM-1 on NK cells in vitro, and the addition of galunisertib, an inhibitor of the TGF-β receptor subunit I, reversed this downregulation. Altogether, our data suggest that the decreased expression of activating receptors NKp30, NKp46, NKG2D, and DNAM-1 on peripheral blood NK cells is positively associated with GC progression, and that TGF-β1-mediated NK cell suppression may be a therapeutically targetable characteristic of GC.